Pengaruh Live Streaming, Shopping Lifestyle, dan Hedonic Shopping Value terhadap Impulsive Buying melalui TikTok Shop dengan Mediasi Price Discount pada Mahasiswa Uin Gusdur Di Pekalongan - Tantowi, Ahmad; Misidawati, Dwi Nova; Nidhom, Misbahun (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
Abstract This study investigates the impact of live streaming, shopping lifestyle, and hedonic shopping value on impulsive buying behavior through TikTok Shop, with price discount acting as a mediator. The research was conducted among students at UIN Gus Dur Pekalongan, utilizing a quantitative approach with a survey method. Data were collected from 250 respondents using structured questionnaires, and analyzed through Structural Equation Modeling (SEM). The results reveal that live streaming positively influences impulsive buying behavior, as it enhances consumer engagement and social interaction during live sessions. Additionally, shopping lifestyle, characterized by active engagement in online shopping, significantly contributes to impulsive buying tendencies. Hedonic shopping value, which focuses on the emotional and enjoyable aspects of shopping, also plays a crucial role in driving impulsive purchases. Furthermore, price discount was found to mediate the relationship between these factors and impulsive buying, amplifying the likelihood of impulsive purchases when combined with attractive offers. The study highlights the importance of live streaming and hedonic value in shaping consumer behavior, particularly among young consumers on social media platforms like TikTok. The findings offer valuable insights for marketers and businesses looking to enhance consumer engagement and drive sales through effective use of live streaming and promotional strategies. Keywords: live streaming, shopping lifestyle, hedonic shopping value, impulsive buying, price discount, TikTok Shop, student behavior, social media marketing